Geology of Setap Shale Formation (Sector 7), Miri, Sarawak, Malaysia - Dahlan, Mohamad Khalil (2016)
Depletion of Conventional reservoir lead to the exploration of the unconventional reservoir which is shale reservoir of known also as shale gas potential. Natural gas in Malaysia was discovered in early 1970’s at the east coast offshore of Peninsular of Malaysia. However, the largest field of gas production were in Sarawak Offshore. Exploration of unconventional shale reservoir in Malaysia is almost unnoticed, compared with the region countries. Setap Shale (Miocene) is in Cycle II and Cycle III of Tertiary sediment based on the previous studies is considerable as matured rock. This study evaluates shale gas potential of Setap Shale. A Sedimentary logging is constructed for the outcrop and Spectral Gamma Ray (SGR) is measured. Several sample are collected for Thin Section analysis, X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM). Result from this project have a contradict data between XRD and SGR where based on XRD lab analysis the clay content for Setap Shale formation for outcrop are illite type whereas from SGR reading shows clay type of smectite.